Genetic variability of forage traits in Paspalum - Pereira, Emerson André; Barros, Thiago; Volkmann, Gabriela Kessler; Battisti, Gabriel Koltermann; Silva, José Antonio Gonzalez da; Simioni, Carine; Dall’Agnol, Miguel (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the genetic variability and the expression of traits of interest for forage production in species of Paspalum. The experiments were carried out in different locations and crop years in randomized block design with three replicates. Five accessions of P. nicorae and two of P. guenoarum were evaluated, besides the cultivar Pensacola (P. notatum), used as a control. The following traits were determined: leaf/stalk ratio; harvest index; and total, leaf, and stalk dray matter. Both main effects (genotype, years, and locations) and the interactions among factors had significant influence on the evaluated traits. The evaluated accessions showed genetic variability in traits of interest for forage production, and their performance varied according to the location and year of cultivation. Total and leaf dry matter production are the traits that most contribute to the detection of the observed genetic variability, regardless of the year of evaluation.